การพัฒนาบทเรียนสำเร็จรูปเพื่อการสอนซ่อมเสริมคณิตศาสตร์ เรื่อง ระบบจำนวนเต็ม สำหรับนักเรียนชั้นมัธยมศึกษาปีที่ 1 ที่มีผลสัมฤทธิ์ทางการเรียนคณิตศาสตร์ต่ำ: The Development of Programmed Instruction for Mathematical Remedial Teaching on System of Integer Numbers for Mathayomsuksa I Students with Low Learning Achievement - Piansawan, Boonya (Asian Health, Science and Technology Reports, 2017)
การวิจัยครั้งนี้ มีจุดมุ่งหมาย เพื่อสร้างและหาประสิทธิภาพ ตามเกณฑ์ 70/70 ของบทเรียนสำเร็จรูปเพื่อการสอนซ่อมเสริมวิชาคณิตศาสตร์ เรื่องระบบจำนวนเต็ม สำหรับนักเรียนชั้นมัธยมศึกษาปีที่ 1ที่มีผลสัมฤทธิ์ทางการเรียนคณิตศาสตร์ต่ำและเพื่อเปรียบเทียบผลสัมฤทธิ์ทางการเรียนวิชาคณิตศาสตร์ เรื่องระบบจำนวนเต็มของนักเรียนชั้นมัธยมศึกษาปีที่ 1ที่มีผลสัมฤทธิ์ทางการเรียนคณิตศาสตร์ต่ำระหว่างก่อนเรียนกับหลังเรียนด้วยบทเรียนสำเร็จรูปนี้ และเพื่อเปรียบเทียบผลสัมฤทธิ์กับเกณฑ์ร้อยละ 70กลุ่มตัวอย่างที่ใช้ในการวิจัยครั้งนี้ เป็นนักเรียนชั้นมัธยมศึกษาปีที่ 1 ที่มีผลสัมฤทธิ์ทางการเรียนวิชาคณิตศาสตร์ต่ำ(ไม่ถึงร้อยละ 50)ในเรื่อง ระบบจำนวนเต็ม จำนวน 18 คนได้มาโดยวิธีการเลือกแบบเจาะจง ผลการวิจัยพบว่า 1. บทเรียนสำเร็จรูปเพื่อการสอนซ่อมเสริมวิชาคณิตศาสตร์ เรื่อง ระบบจำนวนเต็ม สำหรับนักเรียนชั้นมัธยมศึกษาปีที่ 1ที่มีผลสัมฤทธิ์ทางการเรียนคณิตศาสตร์ต่ำได้ผ่านการตรวจสอบความเหมาะสมจากผู้เชี่ยวชาญ จำนวน 5 คน มีความเหมาะสมอยู่ในระดับมาก และมีประสิทธิภาพ 75.07/75.19 ซึ่งสูงกว่าเกณฑ์ 70/70 ที่กำหนดไว้ 2. ผลสัมฤทธิ์ทางการเรียนซ่อมเสริมด้วยบทเรียนสำเร็จรูปนี้ หลังเรียนสูงกว่าก่อนเรียน อย่างมีนัยสำคัญทางสถิติ .053. ผลสัมฤทธิ์ทางการเรียนซ่อมเสริม หลังเรียนด้วยบทเรียนสำเร็จรูปนี้ เป็นไปตามเกณฑ์ร้อยละ 70ที่กำหนดไว้ The purposes of this research were: (i) to develop and test the efficiency ofprogrammed instructionfor Mathematical remedial teaching on system of integer numbers for Mathayomsuksa I students with low learning achievement according to 70/70 basis, (ii) to compare the results of students’ learning achievement on system of integer numbers before and after learning by using this programmed instruction, and (iii) to compare students’ learning achievement after learning by using this programmed instruction with the criterion (70%). The sample groupwas 18 Mathayomsuksa I students with low learning achievement on system of integer numbers (less than 50 %) by purpose sampling. The finding were as follows: 1. The development of programmed instruction for remedial teaching in Mathematics on system of integer numbers for Mathayomsuksa I students with low learning achievement has been approved by five specialists. It is suitable in high level and has the efficiency of 75.07/75.19 which is higher than 70/70 basis. 2. The students’ learning achievement after learning by using this programmed instructionon system of integer numbers forMathayomsuksa Istudents is higher than before learning at the .05 level of significance. 3. The students’ learning achievement after learning by using this programmed instruction on system of integernumbers for Mathayomsuksa I students is statistically notdifferent tothe 70 criterion at the .05 level of significance.